Energy efficient computing architecture for rural applications - Yew, Sin Giap (Universiti Malaysia Sarawak (UNIMAS), 2014)
The introduction of computer technology has brought revolutionary impacts to the community in rural areas. This technology has narrowed the digital divide between the urban and the rural. However, limitation in electricity supply is the major constraint in powering up the Information and Communications Technologies (ICT) equipment in the rural area. Consistent electricity supply is another constraint in deploying computing systems in the rural environment. Rural communities rely heavily on fossil fuel power generator to power up all their electrical and electronic appliances. The problem is the limited operating hours of the power generator and it is not ideal for the continuous long hour operation as the cost of fossil fuel has increased drastically from time to time. Therefore, an energy efficient green computing architecture has been proposed in this research in order to reduce power wastage and make efficient use of the power for consumption by ICT equipments. The proposed architecture can generally be organized into 4 main sections which includes power supply model, computer core components, network connectivity, and remote network computing. Each section has different functionality that takes into consideration of the rural condition and meets the rural requirements. The components involved include solar power inverter, hard disk drive, types of network connections, laptop and netbook. The overall performance shows that an improvement in operating time of up to 315 minutes or 315% can be achieved with the proposed architecture. Hence to increase the sustainability of computing in rural areas, it is important to adopt appropriate computing system architecture.